ANALISIS PENGEMBANGAN KOMPETENSI GURU SDN ROMBEN GUNA II DALAM PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL - Aprillah, Feri; Wahdian, Agus; Ridwan, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Along with the rapid development of technology, the use of digital technology in the world of education is increasingly important to improve the quality of learning. Therefore, teachers' competence in integrating digital technology is the main key in achieving effective and efficient educational goals. This study uses a qualitative approach with literature study methods and interviews with a number of teachers at various levels of education. The results of the analysis show that the development of teachers' competencies in the use of digital technology includes several aspects, including: basic understanding of technology, skills in using educational software and applications, and the ability to manage innovative and interactive learning. In addition, continuous training and support, both from the government and educational institutions, are urgently needed to improve these competencies. This study concludes that the development of teacher competence in digital technology-based learning must be a priority in education policy, teachers the technology in learning process.